Programmed cell death protein-1/programmed death-ligand 1 blockade enhances the antitumor efficacy of adoptive cell therapy against non-small cell lung cancer - Chen, Jingyi; Chen, Yusong; Feng, Fenglan; Chen, Cheng; Zeng, Haikang; Wen, Shuai; Xu, Xin; He, Jianxing; Li, Jin (Journal of Thoracic Disease, 2018)
Background: Cytokine-induced killer (CIK) cells and natural killer (NK) cells are employed by two different approaches to adoptive cell immunotherapy for cancer. It has been reported that adoptive cell immunotherapy could prolong the overall survival (OS) of advanced cancer patients. The introduction of agents that induce immune checkpoint blockades has improved the efficacy of immune-mediated therapy for metastatic cancers. However, the effects of combining a checkpoint inhibitor with CIK cells or NK cells to target non-small cell lung cancer (NSCLC)remain unknown. Methods: The present study investigated the effects of combining CIK cells with a programmed cell death protein-1 (PD-1) inhibitor (an anti-PD-1 monoclonal antibody). During the expansion cultivation, the addition of the PD-1 antibody promoted CIK-mediated cytotoxicity in H1975 lung adenocarcinoma cells. Co-cultivation of CIK cells with the PD-1 antibody for 6 days induced CD3+CD56+ T cell expansion, with increases in the levels of CD107a and interferon γ (IFN-γ). Results: When NK cells were co-cultured with 5 μg/mL of an anti-programmed death-ligand 1 (PD-L1) mAb for 24 hours at an effector cell: target ratio of 10:1, it led to more potent cytotoxicity compared to other time points and concentrations. However, combining NK cells with the anti-PD-L1 mAb showed no significant advantages over treatment with NK cells alone. Conclusions: Our results suggest that combining CIK cells with PD-1 blockade before transfusion might improve the efficiency of CIK therapy for NSCLC patients. This effect does not seem to occur for NK cell therapy.